A carbon nanotube / mesoporous carbon / iron carbide composite wave absorbing material and preparation method thereof

A carbon nanotube/mesoporous carbon/iron carbide composite material addresses the limitations of traditional absorbers by providing lightweight, high-conductivity, and wide-bandwidth electromagnetic wave absorption through controlled nanoparticle distribution and multiple loss mechanisms.

CN114300863BActive Publication Date: 2024-12-13YANTAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111461401.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-02
Publication Date
2024-12-13
Estimated Expiration
2041-12-02

AI Technical Summary

Technical Problem

Traditional electromagnetic wave absorption materials face challenges such as high density, narrow bandwidth, and limited practical application due to their impedance mismatch and attenuation characteristics, hindering their use in electromagnetic stealth technology and health protection.

Method used

A carbon nanotube/mesoporous carbon/iron carbide composite material is prepared through a method involving prepolymerization, imidization, hydrolysis, and pyrolysis, utilizing polyimide self-assembly to achieve uniform distribution of iron carbide nanoparticles on large-diameter carbon nanotubes, forming a lightweight structure with high conductivity and magnetic properties.

Benefits of technology

The composite material exhibits excellent electromagnetic wave absorption performance with ultra-lightweight characteristics, integrating conductive and eddy current loss mechanisms, and achieving wide bandwidth and strong reflection loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114300863B_ABST
    Figure CN114300863B_ABST
Patent Text Reader

Abstract

The present invention discloses a carbon nanotube / mesoporous carbon / iron carbide composite wave absorbing material and a preparation method thereof, wherein the preparation method comprises: adding diamine, dianhydride and organic solvent in a reactor in sequence to carry out prepolymerization reaction to prepare a polyamic acid solution; adding the obtained polyamic acid solution to a carbon nanotube solution uniformly dispersed in advance by ultrasonication, heating under an inert gas to induce an imidization reaction, and filtering to obtain a precipitate A; mixing the obtained precipitate A with ferric nitrate nonahydrate and deionized water uniformly, and then heating to induce a hydrolysis reaction, and filtering to obtain a precipitate B; and subjecting the precipitate B to a high-temperature pyrolysis treatment under an inert atmosphere to obtain a carbon nanotube / mesoporous carbon / iron carbide composite wave absorbing material. The preparation method of the present invention is simple, and the prepared carbon nanotube / mesoporous carbon / iron carbide composite wave absorbing material has excellent wave absorbing properties and ultra-light characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite wave absorbing material and a preparation method, in particular to a carbon nanotube / mesoporous carbon / iron carbide composite wave absorbing material and a preparation method, belonging to the technical field of wave absorbing materials. Background Art

[0002] With the growing demand for electromagnetic stealth technology in the defense field and the threat to human health posed by electromagnetic radiation pollution brought about by the development of electronic information technology, electromagnetic wave absorbing materials have become a major research hotspot in the current materials field.

[0003] The principle of electromagnetic wave absorption is that electromagnetic waves are converted into heat or other forms of energy after entering the electromagnetic wave absorption material, thereby achieving the attenuation of electromagnetic wave energy. However, whether electromagnetic waves can be injected into the electromagnetic wave absorption material and achieve efficient energy conversion depends on the impedance matching and attenuation characteristics of the material. Although traditional electromagnetic wave absorption functional materials (such as iron oxide, etc.) can achieve the purpose of electromagnetic wave absorption, their high density, narrow bandwidth and other problems have limited their practical application.

[0004] Therefore, the development of new nano-composite electromagnetic wave absorbing materials can not only overcome the many problems caused by single absorbing materials, but also meet the requirements of matching electromagnetic wave absorbing materials such as thin thickness, light weight, wide bandwidth, and strong reflection loss. The research is of great significance. Summary of the invention

[0005] The object of the present invention is to provide a carbon nanotube / mesoporous carbon / iron carbide composite absorbing material which has the characteristics of ultra-lightweight and can exhibit excellent electromagnetic wave absorbing performance and a preparation method thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A method for preparing a carbon nanotube / mesoporous carbon / iron carbide composite absorbing material, characterized in that it comprises the following steps:

[0008] Step 1: adding diamine monomer, dianhydride monomer and organic solvent into a reactor, wherein the molar feed ratio of diamine monomer to dianhydride monomer is 1:0.5-1.5, and performing prepolymerization reaction under the condition of inert atmosphere protection and room temperature, the reaction time is 1-24 hours, and a polyamic acid solution is obtained after the reaction is completed;

[0009] Step 2: Disperse the carbon nanotubes into a reaction device filled with an organic solvent, perform ultrasonic treatment for 5 to 40 minutes, then add the polyamic acid solution obtained in step 1, and dilute with an organic solvent, the weight feed ratio of the carbon nanotubes to the polyamic acid solution is 1:0.5 to 2.0, and carry out imidization reaction under the protection of an inert atmosphere at a temperature of 180 to 200° C. for a reaction time of 1 to 24 hours. After the reaction is completed, cool and filter to obtain a precipitate A;

[0010] Step 3: taking the precipitate A obtained in step 2, mixing it with ferric nitrate nonahydrate and deionized water, the mass feed ratio of precipitate A to ferric nitrate nonahydrate is 1:1-2, carrying out a hydrolysis reaction at a temperature of 50-100° C. for 1-24 hours, cooling after the reaction and filtering to obtain a precipitate B;

[0011] Step 4: The precipitate B obtained in step 3 is subjected to pyrolysis treatment under a protective atmosphere at a pyrolysis temperature of 600-900° C. After the pyrolysis treatment, a carbon nanotube / mesoporous carbon / iron carbide composite absorbing material is obtained.

[0012] Preferably, in step 1, the diamine monomer is one or more of ethylenediamine, 4,4′-ethylenediphenylamine, p-phenylenediamine, benzidine and 4,4′-diaminodiphenyl ether; the dianhydride monomer is one or more of pyromellitic anhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride, 4,4′-oxydiphthalic anhydride and 3,4,9,10-tetracarboxylic anhydride; the organic solvent is one or more of N-methylpyrrolidone, dimethyl sulfoxide and N-ethylpyrrolidone; and the protective atmosphere is nitrogen.

[0013] Preferably, in step 2, the organic solvent is one or more of N-methylpyrrolidone, dimethyl sulfoxide and N-ethylpyrrolidone; the protective atmosphere is nitrogen; after the imidization reaction is completed, the precipitate in the reaction device is first filtered with an organic filter membrane, then washed with an organic solvent and anhydrous ethanol in sequence, and finally dried.

[0014] Preferably, in step 3, after the hydrolysis reaction is completed, the precipitate in the reaction device is first filtered with a filter membrane, then washed with deionized water and anhydrous ethanol in sequence, and finally dried.

[0015] Preferably, in step 4, the protective atmosphere is nitrogen; the pyrolysis treatment process is as follows: the heating rate in the first stage is 2 to 5°C / min, and the temperature is kept at 350°C for 1 to 3 hours; the heating rate in the second stage is 2 to 5°C / min, and the temperature is kept at 600 to 900°C for 2 to 4 hours.

[0016] The present invention is beneficial in that:

[0017] (1) The present invention adopts polyimide self-assembly technology to control the preparation of mesoporous carbon layer and iron carbide nanoparticles, and achieves uniform distribution of iron carbide nanoparticles;

[0018] (2) The present invention uses carbon nanotubes with large diameters (150-200 nm) as the supporting skeleton, which has a larger size than single-walled and multi-walled carbon nanotubes, laying the foundation for the construction of ultra-lightweight absorbing materials;

[0019] (3) The carbon nanotube / mesoporous carbon / iron carbide composite absorbing material prepared by the present invention exhibits excellent absorbing performance and ultra-lightweight characteristics in terms of electromagnetic wave absorption;

[0020] (4) The carbon nanotube / mesoporous carbon / iron carbide composite absorbing material prepared by the present invention integrates high conductivity and strong magnetic materials and has a complex heterogeneous interface, which can simultaneously realize multiple loss mechanisms such as conductive loss and eddy current loss. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is an assembly diagram of carbon nanotubes and polyimide in Example 1;

[0022] Figure 2 is a scanning electron microscope image of the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material in Example 1;

[0023] Figure 3 is the XRD pattern of the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material in Example 1;

[0024] Figure 4 is a hysteresis loop diagram of the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material in Example 1;

[0025] Figure 5 is a reflection loss diagram of the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material in Example 1;

[0026] Figure 6 is an assembly diagram of carbon nanotubes and polyimide in Example 6;

[0027] Figure 7 is a scanning electron microscope image of the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material in Example 6;

[0028] Figure 8 is the XRD pattern of the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material in Example 6;

[0029] Fig. 9 is a hysteresis loop diagram of the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material in Example 6;

[0030] Fig.10This is a reflection loss diagram of the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material in Example 6. DETAILED DESCRIPTION

[0031] The present invention utilizes the self-assembly ability of polyimide, realizes the uniform assembly of polyimide on carbon nanotubes by adjusting the polyimide skeleton structure and exhibits different assembly morphologies, and the polyimide assembly can also adjust the uniform distribution of hydrated iron oxide produced by the hydrolysis reaction of iron ions on its surface. Finally, the prepared product is subjected to high-temperature pyrolysis to obtain a carbon nanotube / mesoporous carbon / iron carbide composite wave absorbing material. By adjusting the mesoporous carbon layer structure and the iron carbide content in the nanocomposite material, effective absorption of incident electromagnetic waves can be achieved.

[0032] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0033] Example 1

[0034] Step 1: Prepolymerization

[0035] Pyromellitic anhydride (0.200 g, 0.92 mmol), 4,4′-ethylenediphenylamine (0.195 g, 0.92 mmol) and N-methylpyrrolidone (15 ml) were added into the reactor, and stirred at room temperature for 12 h under nitrogen protection to carry out prepolymerization reaction. After the reaction, a polyamic acid solution was obtained.

[0036] Step 2: Imidization reaction

[0037] A mixture of 0.25 g carbon nanotubes (tube diameter 150-200 nm) and 100 ml N-methylpyrrolidone was ultrasonically treated for 20 min, then added to the polyamic acid solution obtained in step 1, and 50 ml N-methylpyrrolidone was measured with a measuring cylinder to dilute the mixture, and stirred for 3 h under nitrogen protection at a temperature of 200° C. to carry out imidization reaction. After the reaction, the product was cooled first, and then the precipitate in the reaction device was filtered with an organic filter membrane, and then washed with N-methylpyrrolidone and anhydrous ethanol in turn, and finally dried to obtain precipitate A.

[0038] After testing, the assembly of carbon nanotubes and polyimide is shown in Figure 1 .

[0039] Depend on Figure 1 It can be seen that polyimide grows closely on the carbon nanotubes in an assembly structure perpendicular to the carbon nanotubes through crystallization-induced self-assembly.

[0040] Step 3: Hydrolysis reaction

[0041] Take 1 g of the precipitate A obtained in step 2, mix it thoroughly with 1.3 g of ferric nitrate nonahydrate and 500 ml of deionized water, stir it at 80°C for 12 hours, and carry out a hydrolysis reaction. After the reaction is completed, the product is first cooled, then filtered with a filter membrane, and then washed with deionized water and anhydrous ethanol in turn, and finally dried to obtain a precipitate B.

[0042] Step 4: Pyrolysis

[0043] The precipitate B obtained in step 3 was subjected to pyrolysis treatment in a nitrogen atmosphere. Specifically, the first stage heating rate was 2°C / min, from room temperature to 350°C and then kept warm for 1h. The second stage heating rate was 2°C / min, from 350°C to 700°C and then kept warm for 2h. After the pyrolysis treatment, the target composite absorbing material - carbon nanotube / mesoporous carbon / iron carbide composite absorbing material was obtained.

[0044] After testing, the scanning electron microscope image of the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material prepared in this embodiment is shown in Figure 2 , X RD diagram Figure 3 , hysteresis loop diagram see Figure 4 , reflection loss diagram see Figure 5 .

[0045] Depend on Figure 2 It can be seen that the iron carbide particles are evenly distributed on the surface of the target composite absorbing material.

[0046] Depend on Figure 3 It can be seen that iron carbide has a crystalline structure.

[0047] Depend on Figure 4 It can be seen that the target composite absorbing material has strong magnetism.

[0048] Depend on Figure 5 It can be seen that the target composite absorbing material has excellent absorbing performance and ultra-lightweight characteristics.

[0049] Example 2

[0050] Step 1: Prepolymerization

[0051] 3,4,9,10-tetracarboxylic anhydride (0.361 g, 0.92 mmol), 4,4′-ethylenediphenylamine (0.195 g, 0.92 mmol) and N-methylpyrrolidone (20 ml) were added into a reactor, and stirred at room temperature for 24 h under nitrogen protection to carry out a prepolymerization reaction. After the reaction, a polyamic acid solution was obtained.

[0052] Step 2: Imidization reaction

[0053] A mixture of 0.25 g of carbon nanotubes (tube diameter 150-200 nm) and 150 ml of N-methylpyrrolidone was ultrasonically treated for 20 min, then added to the polyamic acid solution obtained in step 1, and 60 ml of N-methylpyrrolidone was measured with a measuring cylinder to dilute the mixture, and stirred for 6 h under nitrogen protection at a temperature of 190° C. to carry out imidization reaction. After the reaction, the product was cooled first, and then the precipitate in the reaction device was filtered with an organic filter membrane, and then washed with N-methylpyrrolidone and anhydrous ethanol in turn, and finally dried to obtain precipitate A.

[0054] It has been detected that polyimide can also be assembled onto carbon nanotubes, but has a different morphology compared to Example 1.

[0055] Step 3: Hydrolysis reaction

[0056] Take 1 g of the precipitate A obtained in step 2, mix it thoroughly with 1.0 g of ferric nitrate nonahydrate and 500 ml of deionized water, stir it at 80°C for 12 hours, and carry out a hydrolysis reaction. After the reaction is completed, the product is first cooled, then filtered with a filter membrane, and then washed with deionized water and anhydrous ethanol in turn, and finally dried to obtain a precipitate B.

[0057] Step 4: Pyrolysis

[0058] The precipitate B obtained in step 3 was subjected to pyrolysis treatment in a nitrogen atmosphere. Specifically, the first stage heating rate was 2°C / min, from room temperature to 350°C and then kept warm for 1 hour. The second stage heating rate was 3°C / min, from 350°C to 800°C and then kept warm for 2 hours. After the pyrolysis treatment, the target composite absorbing material was obtained.

[0059] After testing, the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material prepared in this embodiment has similar appearance structure, magnetism and absorbing properties to those in embodiment 1.

[0060] Example 3

[0061] Step 1: Prepolymerization

[0062] Pyromellitic anhydride (0.200 g, 0.92 mmol), 4,4′-diaminodiphenyl ether (0.184 g, 0.92 mmol) and N-methylpyrrolidone (15 ml) were added into the reactor, and stirred at room temperature for 12 h under nitrogen protection to carry out prepolymerization reaction. After the reaction, a polyamic acid solution was obtained.

[0063] Step 2: Imidization reaction

[0064] A mixture of 0.25 g of carbon nanotubes (tube diameter 150-200 nm) and 100 ml of N-methylpyrrolidone was ultrasonically treated for 30 min, then added to the polyamic acid solution obtained in step 1, and 50 ml of N-methylpyrrolidone was measured with a measuring cylinder to dilute the mixture, and stirred for 4 h under nitrogen protection at a temperature of 200° C. to carry out imidization reaction. After the reaction, the product was cooled first, and then the precipitate in the reaction device was filtered with an organic filter membrane, and then washed with N-methylpyrrolidone and anhydrous ethanol in turn, and finally dried to obtain precipitate A.

[0065] It has been detected that polyimide can also be assembled onto carbon nanotubes, but has a different morphology compared to Example 1.

[0066] Step 3: Hydrolysis reaction

[0067] Take 1 g of the precipitate A obtained in step 2, mix it thoroughly with 1.3 g of ferric nitrate nonahydrate and 500 ml of deionized water, stir it at 80°C for 10 hours, and carry out a hydrolysis reaction. After the reaction is completed, the product is first cooled, then filtered with a filter membrane, and then washed with deionized water and anhydrous ethanol in turn, and finally dried to obtain a precipitate B.

[0068] Step 4: Pyrolysis

[0069] The precipitate B obtained in step 3 was subjected to pyrolysis treatment in a nitrogen atmosphere. Specifically, the first stage heating rate was 2°C / min, from room temperature to 350°C and then kept warm for 1 hour. The second stage heating rate was 2°C / min, from 350°C to 900°C and then kept warm for 2 hours. After the pyrolysis treatment, the target composite absorbing material was obtained.

[0070] After testing, the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material prepared in this embodiment has similar appearance structure, magnetism and absorbing properties to those in embodiment 1.

[0071] Example 4

[0072] Step 1: Prepolymerization

[0073] Pyromellitic anhydride (0.200 g, 0.92 mmol), p-phenylenediamine (0.100 g, 0.92 mmol) and N-methylpyrrolidone (25 ml) were added into the reactor, and stirred at room temperature for 12 h under nitrogen protection to carry out prepolymerization reaction. After the reaction, a polyamic acid solution was obtained.

[0074] Step 2: Imidization reaction

[0075] A mixture of 0.25 g of carbon nanotubes (tube diameter 150-200 nm) and 80 ml of N-methylpyrrolidone was ultrasonically treated for 30 min, then added to the polyamic acid solution obtained in step 1, and 80 ml of N-methylpyrrolidone was measured with a measuring cylinder to dilute the mixture, and stirred for 6 h under nitrogen protection at a temperature of 190° C. to carry out imidization reaction. After the reaction, the product was cooled first, and then the precipitate in the reaction device was filtered with an organic filter membrane, and then washed with N-methylpyrrolidone and anhydrous ethanol in turn, and finally dried to obtain precipitate A.

[0076] It has been detected that polyimide can also be assembled onto carbon nanotubes, but has a different morphology compared to Example 1.

[0077] Step 3: Hydrolysis reaction

[0078] Take 1 g of the precipitate A obtained in step 2, mix it thoroughly with 1.0 g of ferric nitrate nonahydrate and 450 ml of deionized water, stir it at 80°C for 16 hours, and carry out a hydrolysis reaction. After the reaction is completed, the product is first cooled, then filtered with a filter membrane, and then washed with deionized water and anhydrous ethanol in turn, and finally dried to obtain a precipitate B.

[0079] Step 4: Pyrolysis

[0080] The precipitate B obtained in step 3 was subjected to pyrolysis treatment in a nitrogen atmosphere. Specifically, the first stage heating rate was 2°C / min, from room temperature to 350°C and then kept warm for 1 hour. The second stage heating rate was 3°C / min, from 350°C to 800°C and then kept warm for 2 hours. After the pyrolysis treatment, the target composite absorbing material was obtained.

[0081] After testing, the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material prepared in this embodiment has similar appearance structure, magnetism and absorbing properties to those in embodiment 1.

[0082] Example 5

[0083] Step 1: Prepolymerization

[0084] 1,4,5,8-naphthalenetetracarboxylic anhydride (0.247 g, 0.92 mmol), 4,4′-ethylenediphenylamine (0.195 g, 0.92 mmol) and N-methylpyrrolidone (20 ml) were added into a reactor, and stirred at room temperature for 10 h under nitrogen protection to carry out a prepolymerization reaction. After the reaction, a polyamic acid solution was obtained.

[0085] Step 2: Imidization reaction

[0086] A mixture of 0.25 g carbon nanotubes (tube diameter 150-200 nm) and 120 ml N-methylpyrrolidone was ultrasonically treated for 30 min, then added to the polyamic acid solution obtained in step 1, and 40 ml N-methylpyrrolidone was measured with a measuring cylinder to dilute the mixture, and stirred for 4 h under nitrogen protection at a temperature of 190° C. to carry out imidization reaction. After the reaction, the product was cooled first, and then the precipitate in the reaction device was filtered with an organic filter membrane, and then washed with N-methylpyrrolidone and anhydrous ethanol in turn, and finally dried to obtain precipitate A.

[0087] It has been detected that polyimide can also be assembled onto carbon nanotubes, but has a different morphology compared to Example 1.

[0088] Step 3: Hydrolysis reaction

[0089] Take 1 g of the precipitate A obtained in step 2, mix it thoroughly with 0.8 g of ferric nitrate nonahydrate and 500 ml of deionized water, stir it at 80°C for 16 hours, and carry out a hydrolysis reaction. After the reaction, the product is first cooled, then filtered with a filter membrane, and then washed with deionized water and anhydrous ethanol in turn, and finally dried to obtain a precipitate B.

[0090] Step 4: Pyrolysis

[0091] The precipitate B obtained in step 3 was subjected to pyrolysis treatment in a nitrogen atmosphere. Specifically, the first stage heating rate was 2°C / min, from room temperature to 350°C and then kept warm for 2h. The second stage heating rate was 2°C / min, from 350°C to 700°C and then kept warm for 2h. After the pyrolysis treatment, the target composite absorbing material was obtained.

[0092] After testing, the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material prepared in this embodiment has similar appearance structure, magnetism and absorbing properties to those in embodiment 1.

[0093] Example 6

[0094] Step 1: Prepolymerization

[0095] Pyromellitic anhydride (0.200 g, 0.92 mmol), benzidine (0.169 g, 0.92 mmol) and N-ethylpyrrolidone (20 ml) were added into the reactor, and stirred at room temperature for 24 h under nitrogen protection to carry out prepolymerization reaction. After the reaction, a polyamic acid solution was obtained.

[0096] Step 2: Imidization reaction

[0097] A mixture of 0.25 g carbon nanotubes (tube diameter 150-200 nm) and 100 ml N-ethylpyrrolidone was ultrasonically treated for 30 min, then added to the polyamic acid solution obtained in step 1, and 50 ml N-ethylpyrrolidone was measured with a measuring cylinder to dilute the mixture, and stirred for 6 h under nitrogen protection at a temperature of 190° C. to carry out imidization reaction. After the reaction, the product was cooled, and then the precipitate in the reaction device was filtered with an organic filter membrane, and then washed with N-ethylpyrrolidone and anhydrous ethanol in turn, and finally dried to obtain precipitate A.

[0098] After testing, the assembly of large diameter carbon nanotubes and polyimide is shown in Figure 6 .

[0099] Depend on Figure 6 It can be seen that polyimide grows densely on carbon nanotubes through crystallization-induced self-assembly.

[0100] Step 3: Hydrolysis reaction

[0101] Take 1 g of the precipitate A obtained in step 2, mix it thoroughly with 1.3 g of ferric nitrate nonahydrate and 500 ml of deionized water, stir it at 80°C for 12 hours, and carry out a hydrolysis reaction. After the reaction is completed, the product is first cooled, then filtered with a filter membrane, and then washed with deionized water and anhydrous ethanol in turn, and finally dried to obtain a precipitate B.

[0102] Step 4: Pyrolysis

[0103] The precipitate B obtained in step 3 was subjected to pyrolysis treatment in a nitrogen atmosphere. Specifically, the first stage heating rate was 2°C / min, from room temperature to 350°C and then kept warm for 1 hour. The second stage heating rate was 2°C / min, from 350°C to 800°C and then kept warm for 2 hours. After the pyrolysis treatment, the target composite absorbing material was obtained.

[0104] After testing, the scanning electron microscope image of the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material prepared in this embodiment is shown in Figure 7 , X RD diagram Figure 8 , hysteresis loop diagram see Fig. 9 , reflection loss diagram see Fig.10 .

[0105] Depend on Figure 7 It can be seen that the iron carbide particles are evenly distributed on the surface of the target composite absorbing material.

[0106] Depend on Figure 8 It can be seen that iron carbide has a crystalline structure.

[0107] Depend on Fig. 9 It can be seen that the target composite absorbing material has strong magnetism.

[0108] Depend on Fig.10 It can be seen that the absorbing performance of the target composite absorbing material is lower than the absorbing performance of the composite absorbing material prepared in Example 1.

[0109] Example 7

[0110] Step 1: Add 1,4,5,8-naphthalenetetracarboxylic anhydride (0.247 g, 0.92 mmol), ethylenediamine (0.055 g, 0.92 mmol) and N-ethylpyrrolidone (20 ml) into a reactor, stir at room temperature for 24 hours under nitrogen protection to carry out a prepolymerization reaction, and obtain a polyamic acid solution after the reaction.

[0111] Step 2: Imidization reaction

[0112] A mixture of 0.3 g carbon nanotubes (tube diameter 150-200 nm) and 80 ml N-ethylpyrrolidone was ultrasonically treated for 30 min, then added to the polyamic acid solution obtained in step 1, and 70 ml N-ethylpyrrolidone was measured with a measuring cylinder to dilute the mixture. The mixture was heated and stirred in an oil bath at 200° C. for 4 h under nitrogen protection to carry out imidization reaction. After the reaction, the product was cooled first, and then the precipitate in the reaction device was filtered with an organic filter membrane, and then washed with N-ethylpyrrolidone and anhydrous ethanol in turn, and finally dried to obtain precipitate A.

[0113] It has been detected that polyimide can also be assembled onto carbon nanotubes, but has a different morphology compared to Example 1.

[0114] Step 3: Hydrolysis reaction

[0115] Take 1 g of the precipitate A obtained in step 2, mix it thoroughly with 1.3 g of ferric nitrate nonahydrate and 500 ml of deionized water, stir it at 80°C for 10 hours, and carry out a hydrolysis reaction. After the reaction is completed, the product is first cooled, then filtered with a filter membrane, and then washed with deionized water and anhydrous ethanol in turn, and finally dried to obtain a precipitate B.

[0116] Step 4: Pyrolysis

[0117] The precipitate B obtained in step 3 is subjected to pyrolysis treatment in a nitrogen atmosphere. Specifically, the first stage heating rate is 2°C / min, from room temperature to 350°C and then kept warm for 1 hour. The second stage heating rate is 2°C / min, from 350°C to 900°C and then kept warm for 2 hours. After the pyrolysis treatment, the target composite absorbing material is obtained.

[0118] After testing, the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material prepared in this embodiment has similar appearance structure, magnetism and absorbing properties to those in embodiment 1.

[0119] Example 8

[0120] Step 1: Prepolymerization

[0121] 4,4'-oxydiphthalic anhydride (0.310 g, 1.00 mmol), benzidine (0.184 g, 1.00 mmol) and dimethyl sulfoxide (25 ml) were added into the reactor, and stirred at room temperature for 10 h under nitrogen protection to carry out prepolymerization reaction. After the reaction, a polyamic acid solution was obtained.

[0122] Step 2: Imidization reaction

[0123] A mixture of 0.3 g of carbon nanotubes (tube diameter 150-200 nm) and 100 ml of dimethyl sulfoxide was ultrasonically treated for 20 min, then added to the polyamic acid solution obtained in step 1, and 80 ml of dimethyl sulfoxide was measured with a measuring cylinder to dilute the mixture. The mixture was heated and stirred in an oil bath at 200° C. under nitrogen protection for 4 h to carry out imidization reaction. After the reaction, the product was cooled first, and then the precipitate in the reaction device was filtered with an organic filter membrane, and then washed with dimethyl sulfoxide and anhydrous ethanol in turn, and finally dried to obtain precipitate A.

[0124] It has been detected that polyimide can also be assembled onto carbon nanotubes, but has a different morphology compared to Example 1.

[0125] Step 3: Hydrolysis reaction

[0126] Take 1 g of the precipitate A obtained in step 2, mix it thoroughly with 1.5 g of ferric nitrate nonahydrate and 500 ml of deionized water, stir it at 80°C for 8 hours, and carry out a hydrolysis reaction. After the reaction is completed, the product is first cooled, then filtered with a filter membrane, and then washed with deionized water and anhydrous ethanol in turn, and finally dried to obtain a precipitate B.

[0127] Step 4: Pyrolysis

[0128] The precipitate B obtained in step 3 was subjected to pyrolysis treatment in a nitrogen atmosphere. Specifically, the first stage heating rate was 2°C / min, from room temperature to 350°C and then kept warm for 2h. The second stage heating rate was 2°C / min, from 350°C to 800°C and then kept warm for 2h. After the pyrolysis treatment, the target composite absorbing material was obtained.

[0129] After testing, the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material prepared in this embodiment has similar appearance structure, magnetism and absorbing properties to those in embodiment 1.

[0130] It should be noted that the above embodiments do not limit the present invention in any form, and any technical solutions obtained by equivalent replacement or equivalent transformation shall fall within the protection scope of the present invention.

Claims

1. A method for preparing a carbon nanotube / mesoporous carbon / iron carbide composite absorbing material, characterized in that: The following steps are involved: Step 1: adding diamine monomer, dianhydride monomer and organic solvent into a reactor, wherein the molar feed ratio of diamine monomer to dianhydride monomer is 1:0.5-1.5, and performing prepolymerization reaction under the condition of inert atmosphere protection and room temperature, the reaction time is 1-24 hours, and a polyamic acid solution is obtained after the reaction is completed; Step 2: Disperse the carbon nanotubes into a reaction device filled with an organic solvent, perform ultrasonic treatment for 5 to 40 minutes, then add the polyamic acid solution obtained in step 1, and dilute with an organic solvent, the weight feed ratio of the carbon nanotubes to the polyamic acid solution is 1:0.5 to 2.0, and carry out imidization reaction under the protection of an inert atmosphere at a temperature of 180 to 200° C. for a reaction time of 1 to 24 hours. After the reaction is completed, cool and filter to obtain a precipitate A; Step 3: taking the precipitate A obtained in step 2, mixing it with ferric nitrate nonahydrate and deionized water, the mass feed ratio of precipitate A to ferric nitrate nonahydrate is 1:1-2, carrying out a hydrolysis reaction at a temperature of 50-100° C. for 1-24 hours, cooling after the reaction and filtering to obtain a precipitate B; Step 4: The precipitate B obtained in step 3 is subjected to pyrolysis treatment under a protective atmosphere at a pyrolysis temperature of 600-900° C. After the pyrolysis treatment, a carbon nanotube / mesoporous carbon / iron carbide composite absorbing material is obtained.

2. The method for preparing the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material according to claim 1, characterized in that: In step 1, the diamine monomer is one or more of ethylenediamine, 4,4′-ethylenediphenylamine, p-phenylenediamine, benzidine and 4,4′-diaminodiphenyl ether.

3. The method for preparing the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material according to claim 1, characterized in that: In step 1, the dianhydride monomer is one or more of pyromellitic dianhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride, 4,4'-oxydiphthalic anhydride and 3,4,9,10-tetracarboxylic anhydride.

4. The method for preparing the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material according to claim 1, characterized in that: In step 1 and step 2, the organic solvent is one or more of N-methylpyrrolidone, dimethyl sulfoxide and N-ethylpyrrolidone.

5. The method for preparing the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material according to claim 1, characterized in that: In step 1, step 2 and step 4, the protective atmosphere is nitrogen.

6. The method for preparing the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material according to claim 1, characterized in that: In step 2, after the imidization reaction is completed, the precipitate in the reaction device is first filtered with an organic filter membrane, then washed with an organic solvent and anhydrous ethanol in sequence, and finally dried.

7. The method for preparing the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material according to claim 1, characterized in that: In step 3, after the hydrolysis reaction is completed, the precipitate in the reaction device is first filtered with a filter membrane, then washed with deionized water and anhydrous ethanol in sequence, and finally dried.

8. The method for preparing the carbon nanotube / mesoporous carbon / iron carbide composite absorbing material according to claim 1, characterized in that: In step 4, the pyrolysis treatment process is as follows: the heating rate in the first stage is 2-5°C / min, and the temperature is kept at 350°C for 1-3 hours. The heating rate in the second stage is 2-5°C / min, and the temperature is kept at 600-900°C for 2-4 hours.

9. The carbon nanotube / mesoporous carbon / iron carbide composite absorbing material prepared by the preparation method according to any one of claims 1 to 8.